The science of seafaring : the float-tastic facts about ships - Rooney, Anne (2019)
"Introduces the reader to seafaring"--
All at sea -- Where now? -- Moving along -- Ship-shape -- When the wind blows -- Full steam ahead -- Staying afloat -- Carried away -- Waves and wavelength -- The salty sea -- Down in the depths -- Alive, alive oh!
"Published in Great Britain in 2019 by Book House, an imprint of The Salariya Book Company Ltd."
Includes index.
Ages 7+
Keywords: Ships -- Juvenile literature; Shipbuilding -- Juvenile literature; Seafaring life -- Juvenile literature